Pelatihan Kelompok Sadar Wisata: Pembuatan Brosur Desa Wisata Berbahasa Inggris - Anesti Budi Ermerawati; Adaninggar Septi Subekti; Lemmuela Alvita Kurniawati; Arida Susyetina; Mega Wati (Universitas Mathla'ul Anwar Banten, 2022)
TRAINING FOR TOURISM AWARENESS GROUPS: MAKING TOURISM VILLAGE BROCHURES IN ENGLISH. The community service activity was conducted in the form of online training intended for representatives of tourism awareness groups (Pokdarwis). Focusing on enabling the participants to create English brochures promoting their respective tourism villages, the rationale of conducting this training was to empower the participants to be able to advertise the potential of their respective tourism villages to foreigners. The training was conducted in seven sessions from 6 October 2021 up to 1 December 2021. The first session was on the principles of good brochures in terms of design, whilst the next six sessions were on how to write the sections of the brochure in English. The second session was on how to write about villages’ profiles and potentials. The third was on villages’ history and uniqueness. The fourth, fifth, and sixth were on various activities available for visiting tourists. The seventh or last session was the celebration of learning. In conclusion, the training was sufficiently successful despite the low attendance rate. Future programmes could be preceded with more sound needs analysis to ensure not only the relevance of the training materials but also the prospective participants;’ interests in joining such programmes.